KRITIK MATAN TENTANG HADIS–HADIS SEMBELIHAN AQIQAH - Siregar, Dame (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Hadist  of  aqiqoh   is not found in Al-Qur’an and it  is a kind of cutting animal  in Zahiliah as representation of qurban in Adam and Ibrahim Prophets. The Hadist is always contra between on and another where the  hadists  are  sohih  on its quality.  The  Hadist  is contra with  siroh Nabi Muhammad (PBUH).  So,  hadist  on  aqiqah   has been  mansukh  and empowered by hadist forbiding Fatimah and Ali bin Abu Tolib to give aqiqoh on Hasan dan Husain.